2003
DOI: 10.1189/jlb.0503206
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation through CCR5- and CXCR4-mediated gp120-elicited signaling pathways

Abstract: Macrophages are major targets for infection by human immunodeficiency virus type 1 (HIV-1). In addition to their role as productive viral reservoirs, inappropriate activation of infected and uninfected macrophages appears to contribute to pathogenesis. HIV-1 infection requires initial interactions between the viral envelope surface glycoprotein gp120, the cell-surface protein CD4, and a chemokine receptor CCR5 or CXCR4. Besides their role in HIV-1 entry, CCR5 and CXCR4 are G protein-coupled receptors that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 68 publications
(70 reference statements)
3
100
1
Order By: Relevance
“…Because signaling through the TCR inhibits CXCR4-mediated signaling (52), it is possible that prior activation of CD4 ϩ T cells contributes to these differences. Dendritic cells and macrophages are other cell types in which X4 gp120 signals inefficiently and is defective for chemotaxis (23,25,31). One contributing factor is limiting CXCR4 expression in immature dendritic cells (53), and possibly in macrophages (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because signaling through the TCR inhibits CXCR4-mediated signaling (52), it is possible that prior activation of CD4 ϩ T cells contributes to these differences. Dendritic cells and macrophages are other cell types in which X4 gp120 signals inefficiently and is defective for chemotaxis (23,25,31). One contributing factor is limiting CXCR4 expression in immature dendritic cells (53), and possibly in macrophages (54).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the natural ligand of CXCR4, the chemokine stromal cellderived factor 1 (SDF-1) 4 (CXCL12), induced the Erk-1/2 pathway in both stimulated and unstimulated CD4 ϩ T cells (30). Other studies in activated T cells or macrophages showed a defective or limited capacity of gp120 from X4 strains to induce calcium flux and chemotactic responses as compared with gp120 from CCR5-tropic (R5) strains, raising the possibility that gp120 induced an incomplete or aberrant set of signals through CXCR4 (22)(23)(24)31).…”
Section: E Ntry Of Hiv-1 Into Target Cells Requires the Sequential In-mentioning
confidence: 99%
“…In macrophages, early activation is due both to gp120 signalling through CD4 and CCR5 molecules at viral entry and to activation of innate defence mechanisms (cytokines, chemokines, proteases) Lee et al, 2003;Wahl et al, 2003). After a quiescent phase of a few days, viral replication results in further changes in gene expression (Wahl et al, 2003).…”
Section: Macrophage-t Cell Interplay and Hiv-1 Activationmentioning
confidence: 99%
“…In addition to direct human immunodeficiency virus (HIV) type 1 infection of these professional antigen-presenting cells, viral envelope (Env) proteins per se are able to induce a significant impairment of DC function [2][3][4][5][6][7]. The HIV-1 surface glycoprotein, gp 120, is readily shed from the cell surface due to its noncovalent association with the transmembrane Env gp41, exerting modulatory effects on bystander cells through binding to CD4, chemokine receptors or other molecules expressed by DC, such as lectins [8][9][10]. HIV-1 Env proteins were shown to functionally impair isolated primary DC [2,3,11], as well as the in vitro development and maturation of monocyte-derived DC [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%